A mechanical model for spherical fragments penetrating gelatine. (September 2019) - Liu, Kun; Jiang, Mingfei; Wu, Zhilin; Li, Zhongxin; Ning, Jianguo
Highlights: Fragment-muscle tissue interaction is considered and rate-based strength introduced. A mechanical model for spherical fragments penetrating gelatine is established. The model considers inertial resistance, viscous resistance, and target resistance. Results from the model are virtually consistent with experimental results. The model can provide better predictions than those found in the literature. Abstract: The behaviour and effects of a spherical fragment penetrating a simulant and those of biological tissue are similar. To accurately describe the interaction between spherical fragments and muscle tissue, this study first discusses the wounding mechanism and establishes a mechanical model considering the effects of strain rate based on the properties of gelatine, which is a widely used representative simulant in physical surrogates for muscle tissue. Subsequently, experiments wherein gelatine was penetrated by spherical fragments with diameters of 3, 4, and 4.8 mm were conducted. The inertial and viscous resistance coefficients were identified using the least squares method and the experimental results obtained for the 4-mm spherical fragment. Numerical calculations show that the mechanical model agrees well with the experimental values. Further, the mechanical model's ability to adequately describe the motion of spherical fragments penetrating gelatine with good generality is proved. The proposed model can therefore provide a scientific basis for small arms ammunition design and protection evaluation. Graphical abstract: As the fragment penetrates the target, the retarding force on the fragment causes its deceleration and loss of kinetic energy. An application of elementary physical principles leads to the proposal that the retarding force on the fragment can be considered as the sum of three components: first, an inertial component overcoming the inertia of the gelatine that must be moved aside as the fragment penetrates it; second, a viscous component representing the friction on the surface of the fragment, encountered as the fragment slides through the gelatine; and third, the deceleration force owing to the inherent structural characteristics of the target material.Image, graphical abstract